Penatalaksanaan Holistik pada Anak Laki-Laki Usia Lima Tahun dengan Tonsilitis Kronis melalui PendekatanKedokteran Keluarga di Wilayah Puskesmas Simpur - Radharani, Radhika; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2025)
Tonsillitis is an inflammation of the palatine tonsils which are part of Waldeyer's ring. The spread of this infection can occur through the air and hands. It can occur at any age, especially in children. Tonsillitis has been one of the causes of decreased academic achievement and absenteeism from school. This study is a case report. Primary data were obtained through anamnesis (autoanamnesis and alloanamnesis from family and patients), physical examination, and home visits to assess the physical environment. The assessment is based on a holistic diagnosis of the initial, process, and final studies qualitatively and quantitatively. The result obtained is patient An. F, 5 years old with a diagnosis of chronic tonsillitis. Internal risk aspects include the age of the child, patient knowledge, clean and healthy lifestyle, dental and oral hygiene, and poor eating patterns. External risk aspects that affect the patient's condition include the lack of family supervision regarding the consumption of patient snacks, and the slow decision making of follow- up actions from patient complaints, the patient's family does not know about patient’s disease. Furthermore, holistic management of patients and families through the intervention of colored poster media in the form of information about the disease, triggers, and complications. Holistic and comprehensive management of chronic tonsillitis patients with patient centers and family focus methode according to EBM is needed so that they can be managed with therapy and change patient behavior so as to prevent complications.